Pompeio Magno. Italicei qvi Agrigenti negotiantvr - Amela Valverde, Luis (Gerión. Revista de Historia Antigua, 2006)
The important activity of the negotiatores during the Roman Republic is broadly well-known. The Present article analyzed an inscription dedicated by this group of people to Pompey the Great in Rome. In addition in the text, mention of the epigraphs that make allusion to the negotiatores in the West.